Dampak Work-Family Conflicts Dalam Performa Wanita Pekerja: A Systematic Literature Review - Dewi, Meutia; Sugianto; Abd Majid, M. Sabri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
Work-Family Conflict (WFC) is an increasingly common phenomenon faced by working women, especially those who have dual roles as professional workers and homemakers. This study aims to identify and analyze the impact of WFC on the performance of working women through the Systematic Literature Review (SLR) approach using the PRISMA guidelines. The results of the study indicate that WFC has an impact on two main domains, namely work-related impacts (job satisfaction, job stress, fatigue, turnover intention, career adaptation, work innovation, and performance), and non-work-related impacts (psychological well-being, depression, mental disorders, family involvement, parenting self-efficacy, and family harmony) The basis of this classification refers to the theories of Work–Family Enrichment and Conflict by Greenhaus, Beutell, and Powell, which state that conflict can disrupt individual performance, both in work-related areas and in areas unrelated to work (work-related and non-work-related impacts). These findings emphasize the importance of organizational policies and family support in helping working women manage their dual roles. This study recommends strengthening structural and social support to create a sustainable work-family balance.